Comparison between the Use of Clomiphene Citrate and Clomiphene Citrate with Metformin for Ovulation Induction in Women with Polycystic Ovarian Syndrome - رمضان, لينا; سلمان , صفاء; محمد, هبة (Latakia University Journal -Medical Sciences Series, 2020)
Background: Polycystic ovary syndrome is the common cause of an ovulatory infertility. The aim of this research is to compare the efficacy of clomiphene citrate combined with Metformin for ovulation induction in women with PCOS. Materials and Methods: A total of 100 cases with PCOS were studied from December 2018 to December 2019 in Tishreen University Hospital in Lattakia. All of them having chief complain of infertility. They were randomly assigned to receive ovulation induction using clomiphene citrate, 100mg daily for 5 days beginning in the five day of spontaneous or induced mense either alone (Group 1), or in combination with Metformin 1500 mg/day for two months, start a month before the cycle we will use clomiphene citrate in it, and continue in the same dose next month (Group 2). Results: Ovulation rate was higher in Group 2 than Group 1, however without statistically significantly (70% in Group 2 versus 60% in Group 1). With reference to other outcomes: follicle size, endometrial thickness, cervical score were statistically significantly higher in Group 2 than CC alone. Conclution: Our data suggest that combination of Clomiphene Citrate with Metformin increase ovulation rates compared with Clomiphene Citrate alone.